ANALISIS PEMBENTUKAN UNI MONETER ASEAN-5 DENGAN PENDEKATAN PARITAS INTERNASIONAL DALAM HUBUNGAN KESEIMBANGAN NILAI TUKAR JANGKA PANJANG (1980.01 – 2004.12) - Siti Aisyah Tri Rahayu; Lukman Hakim (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2007)
In order to strengthening cooperation regional and form the strength regional in ASEAN, likely require to relate at successful European Union in forming financial and economic market integration (EMU). ME become the “model" a success economic integration. We can conclude that to reach monetary union have to beforehand realized by economic union supported by union and strong politics willingness, where this matter have been blazed the way old in such a way by leaders of European countries of West which is merged into EMU. Intention of this research is to see the international parity condition of Purchasing Power Parity (PPP) and rate of interest parity (UIP) of among currency in ASEAN-5 with the currency of United States. Result of this research obtained is show that the goodness of theory of Purchasing Power Parity (PPP) and rate of interest parity (UIP) cannot be holded for the nations of ASEAN-5. In general, hypothesis ß 1=1 refused by existing data. This fact is indication that PPP and UIP cannot be holded during period 1980.01 until 2004.12. With do not hold of two the parity (PPP and UIP) hence possibility to existing of monetary uni ASEAN likely still will passing sufficient process.